Associations between economic preferences and behavioural health intentions among young adults living in an informal settlement - Andrady, Wayne Jude (University of the Witwatersrand, Johannesburg, 2023)
The emergence of non-communicable diseases in South Africa, most notably among the urban poor, is resulting in an increased burden of diseases. Since NCDs can develop in distinct periods of the life course, post-adolescence-intentions to engage in health behaviours need to be investigated. Furthermore, there is consistent evidence that health behaviours are associated with economic preferences. Yet, it is unclear whether economic preferences are also associated with behavioural health intentions. Objectives: The study aims to examine how risk-taking and patience are associated with behavioural health intentions among young adults in a poor informal urban settlement in South Africa. The study also explores whether there are gender differences in behavioural health intentions and whether these economic preferences contribute to gender gaps in behavioural health intentions. Data and Methods: The study utilized secondary survey data collected from a sample of 240 young adults using a structured questionnaire. The study collected data on behavioural intentions for seven health- protective and health-harming behaviours. Risk-taking and patience are measured using qualitative, quantitative and combined measures from the Global Preference Survey. Ordered probit and seemingly unrelated regression models were estimated and t-tests were employed to quantify gender gaps, followed by the Blinder-Oaxaca decomposition analysis. Findings The study reveals that economic preferences have a moderate association with behavioural health intentions among young adults. However, these results seem contradictory to priori expectations and further research is required. Our findings emphasize the importance of recognizing and addressing the limitations associated with imperfect measures of economic preferences when investigating their association with health behavioural intentions
A Research Report submitted in partial fulfillment of the Degree of Master of Commerce (Economics) School of Economics and Finance, University of the Witwatersrand, 2023
Keywords: Theory of Planned Behaviour; Behavioural health intentions; Economic Preference; Young Adults; Decomposition Analysis; South Africa; UCTD; SDG-3: Good health and well-being